A Review on Microbial Characteristic in Ganges Water: A Review on Microbial Characteristic in Ganges Water - Mukhopadhyay, Goutam (International Journal of Pharmaceutical & Biological Archive, 2018)
This project is mainly done to detect the several growths of harmful microorganisms in river Ganga and their effect on human and other animals. The main criteria of the project are to check the microbial growth in water and their colony characteristics by performing the biochemical tests of the microorganisms. The assessment of the quality of water was done by performing several plots followed by MPN method and the different parameters obtained from them are pH, conductivity of water, DO and biochemical oxygen demand ranges of water, fecal coliform value, and total coliform value. The microorganisms that are generally causes of the pollution of river Ganga are Escherichia coli, Clostridium perfringens, Actinomyces sp., Aerobacter aerogenes, Arcobacter cloacae, Micrococcus sp., Salmonella sp., Staphylococcus aureus, Bacillus sp., Shigella sp., Streptococcus faecalis, diplococcus sp., Proteus vulgaris, Pseudomonas aeruginosa, Klebsiella sp., Clostridium welchii, and Bacillus anthracis. The another causes of pollution of Ganga River are human wastes and industrial hazards. The main criteria of the review are to create a concern throughout the people of India to stop the extensive misuse of River Ganga.